Sosialiasi Manajemen Ritel bagi Siswa/i SMA dan SMK di Kabupaten Nabire - Eveline Komul, Liza Meichy; Uktolseja, Yellia Priciliya; Polii, Julius Denny; Mjesfa, Adrian; Irawan, Immanuel Candra; Latuheru, Melerand Evert (Universitas Pahlawan Tuanku Tambusai, 2024)
The retail industry in Nabire Regency has experienced rapid growth in recent years, driven by the increasing number of trade facilities that support retail activities. This has led to the emergence of opportunities for the absorption of competent human resources in the retail sector. This community service activity utilizes an extension or socialization method with the aim of providing insight (knowledge and understanding) to high school and vocational school students in Nabire Regency about the retail industry and providing an overview of retail industry opportunities that can be utilized in the future. The stages carried out include a pre-test, material delivery, and a post-test. The results of this community service activity show the achievement of implementation with an increase in participants' knowledge about the retail industry.